Linguistic features of postpartum depression using Linguistic Inquiry and Word Count text analysis. Issue 1 (February 2023) - Landoni, Marta; Silverio, Sergio A.; Ciuffo, Giulia; Daccò, Margherita; Petrovic, Milica; Di Blasio, Paola; Ionio, Chiara
Abstract: Objective: This qualitative study examines the linguistic features associated with postpartum depression. Methods: In this longitudinal online study, 53 mothers completed self-report questionnaires assessing symptoms of postpartum depression and an expressive writing exercise about their pregnancy and birth. Mothers were randomly divided into two groups (intervention and control groups). Linguistic Inquiry and Word Count [LIWC] was used to examine the written data for depression and no depression groups. Results: The overall use of words varied depending on the severity of depressive symptoms. Negative emotions and introspective terms were associated with depression and lower use of first-person plural pronouns but not singular pronouns. Additionally, the groups of individuals with depression showed a positive correlation between depressive symptoms and words referring to friends, leisure activities, the body, breastfeeding, exercise, and eating attitudes. Conclusion: In addition to self-disclosure, word analysis and appropriate categorization could be useful for perinatal symptomatology in pregnant women, and interestingly also a meaningful tool that can be taught and used as a preventive care measure among pregnant and postpartum women.